Antioxidant substances in different phenological phases of Psidium guajava L. - Pérez-Pérez, Evelyn Del Carmen (2023)
Introduction. There is worldwide interest in determining the content of plant-based antioxidant substances, and the relationship of the phenological phases of the plant with the production of secondary metabolites. Objective. To determine the effect of phenological phases on the content of antioxidant substances of guava (Psidium guajava L.). Materials and methods. A population sample of 10 % of guava plants from the germplasm bank of CESID-Frutícola y Apícola-CORPOZULIA, located in the municipality of Mara, Zulia state, Venezuela, was evaluated. The content of total phenols (FeT), total flavonoids (FlT), and antioxidant capacity (CA) were determined in dry leaves samples at different phenological phases of the plant, recorded from October 2012 to September 2013. Extraction of the FeT was performed by ultrasound with 0.5 g of dry sample and a methanol: water mixture (80:20 % v/v). For quantification by UV-VIS absorption spectrophotometry, gallic acid for FeT and catechin for FlT were used as standard. The AC was determined by the cation-radical ABTS▪+. Non-parametric statistics were used using SPSS statistical software. Results. The three phenological phases (flowering, fruiting, vegetative sprouting) occurred in guava plants, the reproductive phase prevailed with 38.99 % of flowers and fruits; with higher average presence of vegetative shoots that occurred during the rainy season and the alternation between flowers and fruits production. Intra-population variability was observed in the content of antioxidant substances, FeT content, compared to CA and FlT, was higher in fruiting and in the absence of precipitation. Conclusion. The phenological phases had an effect on the content of antioxidant substances of guava. The fruiting phase had the highest content of total phenols. The contents of total phenols and flavonoids were related to antioxidant capacity.